Testing for Purchasing Power Parity in Cointegrated Panels - Mikael Carlsson; Johan Lyhagen; Pär Österholm (Uppsala University, Department of Economics, 2007)
This paper applies the recently developed maximum-likelihood-panel cointegration method of Larsson and Lyhagen (2007) to test the strong PPP hypothesis during the recent oat period on data for the G7 countries. This method is robust in several important dimensions relative to previous methods, including the well-known issue of cross-sectional dependence of error terms. The findings using this new method are contrasted to those from the Pedroni (1995) cointegration tests and fully modified OLS and dynamic OLS estimators of the cointegrating vectors. Although the shortcomings of previous methods do matter in various cases, the overall results are the same across approaches: The strong PPP hypothesis is forcefully rejected in favor of the weak PPP hypothesis with heterogeneous cointegrating vectors. As a consequence, the strong PPP hypothesis does not even seem to be an acceptable approximation of observed data.
urn:nbn:se:uu:diva-210627
Keywords: C33; F31; 330; Purchasing Power Parity; Panel Cointegration; Maximum Likelihood; Fully Modified OLS; Dynamic OLS; Kaufkraftparität; Panel; Kointegration; Maximum-Likelihood-Methode; G-7-Staaten